Novel cage-like nanoporous ZnO polymorphs with cubic lattice frameworks. (September 2020) - Tuoc, Vu Ngoc; Hong Lien, Le Thi; Huan, Tran Doan; Thao, Nguyen Thi
Highlights: Two novel cage-like nanoporous ZnO polymorphs created by the bottom-up cluster- assembling from the spheroid clusters. Density functional theory proves the structural, dynamical, mechanical stability leading to phases with tuning properties. Promoting design of porous materials for applications needing internal void, e.g. sensor, catalysis or with novel properties. Found an optimal porosity region for gaining the desire strength-to-density figure of merit. Found polytype structures could be extended to other materials and method to potentially find more polytype structures. Abstract: Two cage-like nanoporous polymorphs composed of spheroidal cages (ZnO)24 as building block in high symmetrical cubic lattice frameworks are proposed. By using this cluster, instead of atom, as primary building block we studied various scheme of its assembling via bottom up cluster-cluster coalescence schemes. First principles and density-functional tight binding (DFTB+) calculations confirm that the new polymorphs are energetically, dynamically, and mechanically stable. The two newly found nanoporous phases possess an intrinsic wide direct band gap preserving from wurtzite tetragonal-based bonding. The high cubic symmetry wide bandgap semiconductor and its derivatives are expected to have broad applications in photocatalysis, and biomedicine.